Investigating the lowest threshold of vascular benefits from LDL cholesterol lowering with a PCSK9 mAb inhibitor (alirocumab) in healthy volunteers – a mechanistic physiological study (INTENSITY-LOW): protocol and study rationale. (1st January 2019) - Kostapanos, Michael S.; Cacciottolo, Paul J.; Hubsch, Annette; Pavey, Holly; Hurlock, James; Maki-Petaja, Kaisa; Wilkinson, Ian B.; Cheriyan, Joseph
Abstract: Objective: Whether reducing low density lipoprotein cholesterol (LDL-C) is associated with cardiovascular benefits in low risk normocholesterolaemic subjects is unknown. The INTENSITY LOW [In vestigating the lowest t hreshold of vascular ben efits from LDL-cholesterol lowering with a PCS K9 mAb i nhibit or (alirocumab) in healthy volunteers] study aims to assess whether lowering LDL-C by alirocumab monotherapy can improve endothelial-dependent vascular function compared with placebo (primary objective) in low-risk normocholesterolaemic healthy individuals. Changes in endothelial-dependent or endothelial-independent vascular function, arterial stiffness and biomarkers of systemic inflammation by alirocumab, atorvastatin or their combination are secondary objectives. Study design and methods: This is a single-center, randomized, two-period, single-blind, placebo-controlled clinical trial. The study was registered on clinicaltrials.gov (N03273972). It will include 30 healthy low-risk subjects with LDL-C < 4.1 mmol/l. After passing the screening visit (Visit 1), eligible participants will be randomized 1:1 to either subcutaneous alirocumab 150 mg or placebo. These will be administered as single doses in 2 visits 14 days apart (Visits 2 and 3). Atorvastatin 20 mg once nightly will be prescribed for 14 days at Visit 3 in both groups through to Visit 4. At baseline (Visit 2) and during all post-dose visits (Visits 3–4), endothelial function will be assessed using venous occlusion plethysmography. Specifically, changes in forearm blood flow responses to intra-arterial infusions of acetylcholine, sodium nitroprusside and L-N G -monomethyl-arginine acetate will be assessed as surrogates of endothelial-dependent and -independent vasodilatation. Additionally, arterial stiffness and carotid intima-media thickness will be evaluated at the same timepoints. The above-mentioned changes will be correlated with changes in lipid and systemic inflammation biomarkers.